Comparative transcriptomic analysis of gonadal development and renewal in the ovoviviparous black rockfish (Sebastes schlegelii) - Jianshuang Li (BMC, 2021)
Abstract Background The black rockfish (Sebastes schlegelii) has an ovoviviparous reproductive pattern and long-term sperm storage, resulting in asynchronous gonadal development between the sexes. However, the comprehensive understanding of gonadal development in black rockfish has not yet been achieved. Here, we studied gonadal development and germ cell renewal using histology and RNA-seq. Results In this study, RNA-seq was performed on testes and ovaries to characterize key pathways and genes that are active during development and gamete maturation in black rockfish. Differentially expressed genes (DEGs) were identified and annotated in 4 comparisons (F_III vs. F_IV, F_IV vs. F_V, M_III vs. M_IV and M_IV vs. M_V). Based on analysis of DEGs enriched in the testis, 11 and 14 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were mapped to the M_III vs. M_IV group and the M_IV vs. M_V group, respectively. DEGs in ovarian development were also classified into 10 groups according to their biological functions. The expression patterns of the selected genes determined by qPCR were significantly correlated with the RNA-Seq results, supporting the reliability and accuracy of the RNA-Seq analysis. E2 levels showed down regulation from previtellogenesis to mature stage in female and T level showed down regulation from spermatogenesis to regressed stage in the male. Conclusions The categories “intercellular interaction and cytoskeleton”, “molecule amplification” and “repair in the cell cycle” were revealed to be crucial in testis development and spermatogenesis, as was the biosynthesis of a series of metabolites. Our results provide comprehensive insight into black rockfish gonadal development and provide a basis for further study of reproductive physiology and molecular biology in ovoviviparity teleosts.